Experimental test and hysteretic behavior of single cross-arm PCS-BRBs. (September 2019) - Guo, Yan-Lin; Zhou, Peng; Fu, Peng-Peng; Zhu, Bo-Li; Wang, Meng-Zheng
Abstract: An innovative buckling-restrained brace (BRB) is devised by imposing a cable stayed system (CSS) on a common BRB, namely single cross-arm pre-tensioned cable-stayed buckling-restrained brace (SPCS-BRB). Its overall external stiffness thus load-bearing capacity can be dramatically enhanced over the common BRB. A previous study conducted by the authors investigated comprehensively the elastic buckling behavior of the brace, yet experimental investigations and detailed design suggestions were not provided. Two SPCS-BRB specimens have been devised and tested. Test results revealed that both specimens possessed excellent hysteretic response with stable hysteretic curves, which fulfilled the ductility requirement specified in the AISC seismic provisions. The adopted simplified Finite Element (FE) model for experimental simulations corresponds well with the obtained test results. Moreover, additional FE analysis (FEA) has been conducted on the SPCS-BRBs subjected to monotonic and cyclic axial loads, respectively as to validate the test results further. In addition, threshold values of restraining ratios are obtained by guaranteeing the cables to remain tensioned prior to attaining ultimate failures, and ensuring maximum load resistance of the SPCS-BRBs is obtained. It is observed from the FEA that global instability failures of the SPCS-BRBs are caused by expansion of yielding at the extreme fibers of the external tube. Finally, FEA has been conducted on the load resistance of the SPCS-BRBs by considering the effect of interactive buckling and prestressing force of cables. It is found that interactive buckling could become critical in dominating the load resistance of the SPCS-BRBs when single-wave symmetric buckling mode is considered. Highlights: Hysteretic responses of two SPCS-BRB specimens were experimentally investigated. Stable and ample hysteretic curves were obtained for the two specimens. Experimental results corresponded well with finite element (FE) simulations. FE analysis (FEA) was conducted on load resistance and hysteretic performance of SPCS-BRBs. Additional FEA was conducted on load resistance of SPCS-BRBs considering interactive buckling.